2020
DOI: 10.1101/2020.08.26.20157297
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of a qualitative real-time RT-PCR assay for the detection of SARS-CoV-2: A guide and case study in setting up an emergency-use, laboratory-developed molecular assay

Abstract: Developing and deploying new diagnostic tests is difficult, but the need to do so in response to a rapidly emerging pandemic such as COVID-19 is crucially important for an effective response. In the early stages of a pandemic, laboratories play a key role in helping health care providers and public health authorities detect active infection, a task most commonly achieved using nucleic acid-based assays. While the landscape of diagnostics is rapidly evolving, polymerase chain reaction (PCR) remains the gold-sta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…To detect SARS-CoV-2 using RT-LAMP, we took advantage of the primer set previously validated in vitro by Zhang et al . 24 and tested, on clinical specimens from large cohorts of COVID-19 patients, by several other authors 16 19 . The primer set (N-A) targeted the N gene, which encodes the nucleocapsid protein and has the most abundant expression of subgenomic mRNA during infection 32 35 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To detect SARS-CoV-2 using RT-LAMP, we took advantage of the primer set previously validated in vitro by Zhang et al . 24 and tested, on clinical specimens from large cohorts of COVID-19 patients, by several other authors 16 19 . The primer set (N-A) targeted the N gene, which encodes the nucleocapsid protein and has the most abundant expression of subgenomic mRNA during infection 32 35 .…”
Section: Resultsmentioning
confidence: 99%
“…Several authors have recently shown that the use of different primer sets boosts RT-LAMP sensitivity, possibly due to better primer efficiency and/or higher target abundance. Also different saliva treatment protocols, combining certain chemicals and proteinase K, have been shown to improve SARS-CoV-2 detection in saliva samples 16 , 21 , 22 , 28 , 29 , 31 . Thus, we reason that there is still room to improve the sensitivity of our test.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory real-time (RT)-PCR represents the standard of care for the detection of the SARS-CoV-2 infection [6,7], but this technique is time-consuming (up to 24 h for the result), not always available, and the technical requirements usually can only be met by centralized diagnostic laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory real-time (RT)-PCR represents the standard of care for the detection of the SARS-CoV-2 infection [6,7], but this technique is time-consuming (up to 24 hours for the result), not always available, and the technical requirements usually can only be met by centralized diagnostic laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Different diagnostic strategies are now available to identify or exclude a current infection, identify people in need of care escalation, or to test for past infection and immune response [4,5]. Laboratory real-time (RT)-PCR represents the standard of care for the detection of the SARS-CoV-2 infection [6,7], but this technique is time-consuming (up to 24 hours for the result), not always available, and the technical requirements usually can only be met by centralized diagnostic laboratories.…”
Section: Introductionmentioning
confidence: 99%